Long-term clinical outcomes of stereotactic radiosurgery and hypofractionated stereotactic radiotherapy using the CyberKnife® robotic radiosurgery system for vestibular schwannoma - Putipun Puataweepong (2022)
Aim: The study aimed to evaluate the long-term clinical outcomes of patients with vestibular schwannoma (VS) treated with stereotactic radiosurgery (SRS) and hypofractionated stereotactic radiotherapy (HSRT) with frameless robotic whole-body radiosurgery system (CyberKnife®). Methods: This retrospective analysis of prospectively collected data included 123 consecutive patients with VS treated at the Radiosurgery center, Ramathibodi Hospital, Bangkok, Thailand. SRS was recommended for patients with unserviceable hearing and Koos grade I–III tumors, and HSRT for patients with serviceable hearing or Koos grade III–IV tumors. Between March 2009 and December 2015, 23 patients (19%) were treated with SRS, whereas 100 (81%) received HSRT. The commonly used regimen was 12 Gy in one fraction for SRS and 18 Gy in three fractions for HSRT. Results: After a median follow-up of 72 months (range: 12–123 months), the 5-year and 8-year progression-free survival (PFS) rates for the whole cohort were 96% and 92%, respectively. The PFS was not significantly different between the SRS and HSRT groups (p = 0.23). Among 28 patients with serviceable hearing in the HSRT group, the 5-year and 8-year hearing preservation rates were 87% and 65%, respectively. The rate of nonauditory complications was 14%. Koos grade III/IV was a predictor of disease progression and was associated with nonauditory complications. Conclusion: SRS and HSRT with the CyberKnife® system provided excellent long-term tumor control with a low rate of nonauditory complications. HSRT may result in acceptable hearing preservation rates.